PTH-336 Effects of lower doses of dca on radiosensitisation of colorectal cancer cells in vitro. (22nd June 2015) - Shaikh, S; Juan, B San; Hughes, T; Perry, SL; Maisey, T; Jayne, DG
Abstract : Introduction: Neoadjuvant radiotherapy confers a well-established benefit in locoregional recurrence for patients with locally invasive rectal cancer. However, only around 50% experience significant downstaging of their tumour. Radiation-associated toxicity renders dose escalation unachievable. Dichloroacetate (DCA) is a generic drug shown to modify tumour metabolism reversing the Warburg effect and inducing apoptosis and may potentially enhance the effect of radiation. This study aimed to investigate the effects of DCA at lower doses in combination with radiotherapy on the survival of CRC cell lines, and any possible synergistic DNA damage. Method: CRC cells (LoVo) and control cells (HEK 293) treated with DCA (2, 5, 10 mM) and irradiation (0, 4, 8 Gy). Influences of the combination treatment on cell survival were analysed using MTT assays and clonogenic assays and the induction of DNA damage by quantifying gamma-H2AX foci. Statistical analyses were performed using GraphPad, differences between DCA-treated and vehicle control groups were assessed using the Mann-Whitney U test. Results: DCA (5 mM) significantly reduced the survival of CRC cells in combination with 4 Gy and 8 Gy (P = 0.0244, 0.0078, respectively). DCA (10 mM) significantly reduced survival of CRC cells in in combination with 4 Gy and 8 Gy (P < 0.0001, <0.0001, respectively). DCA (5 mM) significantly increased the mean number of DNA double-strand breaks (DSB) per CRC cell in combination with 4 Gy and 8 Gy (P = 0.0041, 0.023, respectively). In unirradiated CRC cells, all the DCA doses (2, 5, 10 mM) significantly increased the mean number of DSB's per CRC cell (P < 0.0014). In the control cell line DCA (5, 10 mM) significantly increased the mean number of DSB's per cell induced at 4 Gy (P < 0.0001). Conclusion: Lower doses of DCA may have an additive killing effect in combination with radiation in CRC cells. A similar picture of sensitivity was seen in normal cell line demonstrating that DCA is not completely harmless. Increasing doses of DCA associated with increased levels of DSB's in CRC cells and it may be a potential mechanism behind DCA. Further research is warranted exploring the mechanism behind the effects of DCA and as a potential adjunct in the management of rectal cancers. Disclosure of interest: None Declared.